It - King, Stephen, 1947- (Hodder & Stoughton Ltd., 2017)
They were seven teenagers when they first stumbled upon the horror. Now they were grown-up men and women who had gone out into the big world to gain success and happiness. But none of them could withstand the force that drew them back to Derry, Maine to face the nightmare without an end, and the evil without a name.